Recent advances in masonry modelling : micromodelling and homogenisation - Lourenço, Paulo B. (2010)
The mechanics of masonry structures have been for long underdeveloped in comparison with other fields of knowledge, being presently, non-linear analysis a very popular field in research. Masonry is a composite material made with units and mortar, which presents a clear micro-structure. The issue of mechanical data necessary for advanced non-linear analysis is addressed first, with a set of recommendations. Then, the possibilities of using micro-modeling strategies replicating units and joints are addressed, with a focus on an interface finite element model for cyclic loading and a limit analysis model. Finally, homogenization techniques are addressed, with a focus on a model based on a polynomial expansion of the micro-stress field. Application examples of the different models are also given.